Environmental determinants of reef fish community structure in Sempu Strait, East Java, Indonesia - ANDIK ISDIANTO; KHALIL GIBRAN; ADE YAMINDAGO; SYARIFAH HIKMAH JULINDA SARI; ADI TIYA YANUAR; DESY SETYONINGRUM; ARIEF SETYANTO; LISA NUR HIDAYAH; KRISTINA MARSELA; MUCHAMAD FAIRUZ HAYKAL; AULIA LANUDIA FATHAH; BERLANIA MAHARDIKA PUTRI; SUPRIYADI SUPRIYADI; OKTIYAS MUZAKY LUTHFI; DWI CANDRA PRATIWI (Society for Indonesian Biodiversity, 2024)
Abstract. Isdianto A, Gibran K, Yamindago A, Sari SHJ, Yanuar AT, Setyoningrum D, Setyanto A, Hidayah LN, Marsela K, Haykal MF, Fathah AL, Putri BM, Supriyadi, Luthfi OM, Pratiwi DC. 2024. Environmental determinants of reef fish community structure in Sempu Strait, East Java, Indonesia. Biodiversitas 25: 4781-4789. The Rumah Apung located in Sempu Strait, Malang District, East Java, Indonesia, is home to diverse coral reef ecosystems that provide vital ecological services and support local livelihoods. However, these ecosystems face significant threats from both natural environmental changes and anthropogenic activities. Understanding how environmental factors influence reef fish communities is critical to inform effective conservation strategies. This study investigated the influence of environmental factors on the community structure of coral reef fish in the Sempu Strait waters, East Java, using Underwater Visual Census (UVC) and Principal Component Analysis (PCA). Conducted from August 2023 to May 2024 at the Sempu Strait Floating House Station, this study aimed to assess the impact of water quality, substrate type, and food availability on the diversity and abundance of coral reef fish. The main results revealed a significant correlation between the community structure of coral reef fish and environmental variables such as water clarity, salinity (r = 0.65, p<0.01), pH (r = 0.55, p<0.05), dissolved oxygen (r = 0.70, p<0.01), and sediment type. Seasonal variations significantly affected water quality, with cold nutrient-rich water during the east monsoon increasing fish biomass by about 30%. Human activities, especially recreational diving and fishing activities, were correlated with a 20% decline in coral reef fish populations, highlighting the anthropogenic pressure on this ecosystem. PCA provides insight into the complex interdependencies within coral reef ecosystems, illustrating how multiple environmental factors combine to influence reef fish dynamics. The study concludes that effective management and conservation strategies, such as establishing marine protected areas, implementing community-based monitoring programs, and promoting sustainable tourism practices, are essential, supported by regular environmental monitoring, are essential to maintain the biodiversity and ecological integrity of coral reefs in the Sempu Strait. These strategies should address both natural environmental changes and anthropogenic impacts to mitigate their adverse effects on coral reef ecosystem conditions.